Preparation method of carbohydrate-based sodium ion battery hard carbon negative electrode material

Through spray drying and phased heat treatment, cross-linked structures are formed, combined with low temperature and high temperature sintering, the melting and foaming problems of carbohydrate precursors in the early stage of pyrolysis are solved, and the preparation of hard carbon negative electrode materials with high sodium storage capacity and excellent purity is achieved.

CN119706805AActive Publication Date: 2025-03-28SHENZHEN JANAENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411964713.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Carbohydrate precursors are prone to melt, foam and expand in the early stages of pyrolysis, resulting in difficult processing, high energy consumption and low yield, and form a structure with poor electrochemical performance during high-temperature sintering, and low sodium storage capacity.

Method used

The crosslinked structure is formed by spray drying and phased heat treatment to avoid melting and foaming, followed by low- and high-temperature sintering to form a developed internal pore structure and increase the sodium storage capacity.

Benefits of technology

It achieves high sodium storage capacity, excellent product purity and green and environmentally friendly processes, and improves the electrochemical performance and processability of hard carbon materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbohydrate-based sodium ion battery hard carbon negative electrode material, which comprises the following steps: S1, premixing raw materials: mixing a carbohydrate precursor, a stabilizer, a cross-linking agent, a defoaming agent, deionized water and ethanol to obtain a mixed solution; s2, spray drying: drying the mixed solution by spray drying to obtain a mixed precursor; s3, cross-linking reaction: carrying out staged heat treatment on the mixed precursor to obtain a cross-linked precursor; s4, crushing and refining: crushing the cross-linked precursor to obtain a refined cross-linked precursor; s5, low-temperature sintering: carrying out low-temperature sintering on the cross-linked precursor in a protective atmosphere to obtain a pre-carbonized material; and S6, high-temperature sintering: carrying out high-temperature sintering on the pre-carbonized material in a protective atmosphere to obtain the sodium-ion battery hard carbon negative electrode material. The preparation method of the carbohydrate-based sodium ion battery hard carbon negative electrode material has the characteristics of high sodium storage capacity, excellent product purity and green and environment-friendly process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material. Background Art

[0002] Compared with traditional lithium-ion batteries, sodium-ion batteries have outstanding advantages in safety performance, low-temperature performance, high-temperature performance, and rate performance. They are expected to partially replace lithium-ion batteries in sub-sectors such as start-stop power supplies, large-scale energy storage, household energy storage, and low-speed two-wheeled vehicles, and play an important role.

[0003] In terms of negative electrode materials for sodium-ion batteries, hard carbon negative electrode materials are currently the first choice for industrialization. The properties of the hard carbon precursor play a decisive role in the structure and electrochemical properties of the final hard carbon material. Therefore, the selection of the hard carbon precursor is the key to current industrialization.

[0004] At present, the hard carbon precursors commonly used in sodium-ion batteries are mainly resins (polyfurfuryl alcohol, phenolic resin, etc.), fossils (natural asphalt, petroleum asphalt, coal tar, coal, etc.) and biomass (coconut shell, walnut shell, lignin, carbohydrates, etc.). Among them, biomass precursors have the advantages of a wide range of raw material sources, low prices, and renewability, and are currently the layout direction of most negative electrode manufacturers.

[0005] In addition to the above advantages, carbohydrate precursors in biomass (specifically including glucose, sucrose, cellulose, starch, etc.) also have the advantages of good consistency and low ash content. They do not require the use of large amounts of acid to purify and reduce the ash content, and therefore have attracted much attention.

[0006] However, carbohydrate precursors will melt, foam, expand severely and easily stick to the equipment in the early stage of pyrolysis, resulting in difficult processing, high energy consumption and low yield. In addition, carbohydrate components tend to form structures with small interlayer spacing and large pore size during high-temperature sintering, resulting in poor electrochemical performance. The sodium storage capacity is low. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, which has the characteristics of high sodium storage capacity, excellent product purity and green process.

[0008] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: mixing a carbohydrate precursor, a stabilizer, a crosslinking agent, a defoaming agent, deionized water and ethanol to obtain a mixed solution; S2, spray drying: using spray drying to dry the mixed solution obtained in step S1 to obtain a mixed precursor; S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor; S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor; S5, low temperature sintering: sintering the cross-linked precursor obtained in step S4 at low temperature under a protective atmosphere to obtain a pre-carbonized material; S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery.

[0009] Furthermore, in step S3, the first stage of the staged heat treatment has a treatment temperature of 120-160°C and a treatment time of 2-5 hours; the second stage of the stage of the heat treatment has a treatment temperature of 150-250°C and a treatment time of 2-8 hours.

[0010] Specifically, the treatment temperature of the first stage is lower than the decomposition temperature of the defoamer and higher than the decomposition temperature of the carbohydrate. In this process, the treatment temperature is higher than the melting point of the carbohydrate, but the morphology of the stabilizer remains basically unchanged at this temperature, so the molten carbohydrate is adsorbed on the surface of the stabilizer, and under the support of the stabilizer, the precursor is not melted and always maintains a good powdery state. In this process, the carbohydrate decomposes in large quantities and produces a large amount of volatile gases. Under the action of the defoamer, the purpose of no foaming and no expansion is achieved. The treatment temperature of the second stage is higher than the decomposition temperature of the defoamer and lower than the combustion temperature of the carbohydrate. In this process, the hydrogen bond network in the carbohydrate is destroyed under the action of oxygen, and a large number of active hydroxyl groups are released, and the active hydroxyl groups react with the hydroxyl groups in the cross-linking agent to form a cross-linked structure. In addition, the chemical bonds with poor thermal stability continue to break to produce a large amount of escaping gas, and a developed interconnected pore structure is formed inside the carbon material during the gas escape process.

[0011] Furthermore, in step S1, the stabilizer is one or more of phenolic resin, epoxy resin, polyimide, polyfurfuryl alcohol, and lignin; the amount of the stabilizer added is 1-10wt.% of the amount of the carbohydrate precursor added; specifically, the stabilizer is a carbon-containing raw material rich in polycyclic aromatic hydrocarbons. Polycyclic aromatic hydrocarbons have good thermal stability and a high pyrolysis temperature. The morphology remains basically unchanged at a certain temperature, so it can be used as a proppant to keep the morphology of the entire system unchanged.

[0012] Furthermore, in step S1, the cross-linking agent is one or more of phosphoric acid, metaphosphoric acid, pyrophosphoric acid and sulfuric acid; the amount of the cross-linking agent added is 5-20wt.% of the amount of the carbohydrate precursor added.

[0013] Furthermore, in step S1, the defoaming agent is one or more of polyvinyl pyrrolidone, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, fatty alcohol polyethylene glycol ester, fatty acid glyceride, and polyol; the added amount of the defoaming agent is 0.5-3 wt.% of the added amount of the carbohydrate precursor.

[0014] Furthermore, in step S1, the amount of ethanol added is 5-20 wt.% of the amount of carbohydrate precursor added. Specifically, the purpose of adding ethanol is to increase the solubility of the stabilizer in the mixed solution. The amount of ethanol added will affect the effect of the present invention: if the amount of ethanol added is too low, the stabilizer is not easy to be evenly dispersed in the mixed solution; if the amount of ethanol added is too high, the carbohydrate and the cross-linking agent are not easy to dissolve in the mixed solution, resulting in an uneven structure of the synthesized hard carbon product and poor product consistency.

[0015] Further, in step S6, the protective atmosphere is nitrogen and / or argon, the sintering temperature is 900-1600°C, and the sintering time is 2-6 hours. In this process, the pre-carbonized material is further graphitized at high temperature, and an ordered carbon layer is gradually formed, forming a developed internal pore structure wrapped by a curved carbon layer.

[0016] Further, in step S2, the outlet air temperature of the spray drying is 110-150°C, and the inlet air temperature is 200-320°C. In the spray drying process, after the mixed liquid is atomized, the water is rapidly vaporized and evaporated in the process of contact with hot air to obtain a dry sample. Due to the fast evaporation rate of water, the mixed liquid can still maintain the uniformity before drying.

[0017] Furthermore, in step S1, the carbohydrate precursor is one or more of glucose, sucrose, fructose, galactose, starch, cellulose, curdlan, dextran, arabinan, and xylose.

[0018] Furthermore, in step S4, the crushing method is one or more of mechanical grinding, air flow grinding, Raymond milling, ball milling, and stirring milling, and the material is crushed to a D50 of 3-10 μm.

[0019] Further, in step S5, the protective atmosphere is nitrogen and / or argon, the sintering temperature is 400-800° C., and the sintering time is 1-5 hours.

[0020] The present invention provides a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, which has the following beneficial effects: First, high sodium storage capacity: the carbohydrate precursor forms a relatively stable cross-linked structure under the action of oxygen and cross-linking agent, and a developed interconnected pore structure is formed inside the cross-linked structure during gas escape, thereby improving the sodium storage capacity of the hard carbon material; Second, the product purity is excellent. Compared with other types of biomass-based hard carbon materials, carbohydrate raw materials have a definite and uniform chemical structure and a low impurity content, which effectively improves the purity of the material; Third, the process is green and environmentally friendly. Since the content of metal impurities in the raw materials is very low, there is no need for additional pickling and purification process, and there is no need to use a large amount of acid. The process is simple and green and environmentally friendly. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0022] The present invention discloses a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: mixing a carbohydrate precursor, a stabilizer, a crosslinking agent, a defoaming agent, deionized water and ethanol to obtain a mixed solution; S2, spray drying: using spray drying to dry the mixed solution obtained in step S1 to obtain a mixed precursor; S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor; S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor; S5, low temperature sintering: sintering the cross-linked precursor obtained in step S4 at low temperature under a protective atmosphere to obtain a pre-carbonized material; S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery.

[0023] Furthermore, in step S3, the first stage of the staged heat treatment has a treatment temperature of 120-160°C and a treatment time of 2-5 hours; the second stage of the stage of the heat treatment has a treatment temperature of 150-250°C and a treatment time of 2-8 hours.

[0024] Furthermore, in step S1, the stabilizer is one or more of phenolic resin, epoxy resin, polyimide, polyfurfuryl alcohol, and lignin; and the amount of the stabilizer added is 1-10 wt.% of the amount of the carbohydrate precursor added.

[0025] Furthermore, in step S1, the cross-linking agent is one or more of phosphoric acid, metaphosphoric acid, pyrophosphoric acid and sulfuric acid; the amount of the cross-linking agent added is 5-20wt.% of the amount of the carbohydrate precursor added.

[0026] Furthermore, in step S1, the defoaming agent is one or more of polyvinyl pyrrolidone, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, fatty alcohol polyethylene glycol ester, fatty acid glyceride, and polyol; the added amount of the defoaming agent is 0.5-3 wt.% of the added amount of the carbohydrate precursor.

[0027] Furthermore, in step S1, the amount of ethanol added is 5-20 wt.% of the amount of carbohydrate precursor added.

[0028] Further, in step S6, the protective atmosphere is nitrogen and / or argon, the sintering temperature is 900-1600° C., and the sintering time is 2-6 hours.

[0029] Furthermore, in step S2, the outlet air temperature of the spray drying is 110-150°C, and the inlet air temperature is 200-320°C.

[0030] Furthermore, in step S1, the carbohydrate precursor is one or more of glucose, sucrose, fructose, galactose, starch, cellulose, curdlan, dextran, arabinan, and xylose.

[0031] Furthermore, in step S4, the crushing method is one or more of mechanical grinding, air flow grinding, Raymond milling, ball milling, and stirring milling, and the material is crushed to a D50 of 3-10 μm.

[0032] Further, in step S5, the protective atmosphere is nitrogen and / or argon, the sintering temperature is 400-800° C., and the sintering time is 1-5 hours.

[0033] Example 1 This embodiment relates to a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: Mix carbohydrate precursors, stabilizers, crosslinkers, defoamers, deionized water and ethanol to obtain a mixed solution. Specifically, the carbohydrate precursors are dextran, arabinan and xylose; the stabilizers are polyfurfuryl alcohol and lignin, and the amount of stabilizers added is 5wt.% of the amount of carbohydrate precursors added; the crosslinkers are metaphosphoric acid, pyrophosphoric acid and sulfuric acid, and the amount of crosslinkers added is 5wt.% of the amount of carbohydrate precursors added; the defoamers are polyvinyl pyrrolidone and polyethylene glycol, and the amount of defoamers added is 3 wt.% of the amount of carbohydrate precursors added; the amount of ethanol added is 10 wt.% of the amount of carbohydrate precursors added.

[0034] S2, spray drying: using spray drying to dry the mixed solution obtained in step S1 to obtain a mixed precursor. Specifically, the outlet air temperature of the spray drying is 130°C and the inlet air temperature is 200°C.

[0035] S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor. Specifically, the first stage of the staged heat treatment is at a temperature of 140° C. for 2 hours, and the second stage is at a temperature of 250° C. for 5 hours.

[0036] S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor. Specifically, the crushing method is ball milling or stirring milling, and the material is crushed to a D50 of 3-10 μm.

[0037] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen, the sintering temperature is 600° C., and the sintering time is 1 hour.

[0038] S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery. Specifically, the protective atmosphere is argon, the sintering temperature is 1200° C., and the sintering time is 2 hours.

[0039] Example 2 This embodiment relates to a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: Mix carbohydrate precursors, stabilizers, crosslinkers, defoamers, deionized water and ethanol to obtain a mixed solution. Specifically, the carbohydrate precursors are galactose, starch, cellulose, curdlan, dextran, arabinan, and xylose; the stabilizers are phenolic resin, polyimide, polyfurfuryl alcohol, and lignin, and the amount of stabilizer added is 1wt.% of the amount of carbohydrate precursor added; the crosslinkers are pyrophosphoric acid and sulfuric acid, and the amount of crosslinker added is 20wt.% of the amount of carbohydrate precursor added; the defoamers are polyvinyl pyrrolidone, polyethylene glycol, fatty acid glyceride, and polyols, and the amount of defoamer added is 2 wt.% of the amount of carbohydrate precursor added; the amount of ethanol added is 5 wt.% of the amount of carbohydrate precursor added.

[0040] S2, spray drying: spray drying is used to dry the mixed solution obtained in step S1 to obtain a mixed precursor. Specifically, the outlet air temperature of the spray drying is 110°C and the inlet air temperature is 320°C.

[0041] S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor. Specifically, the first stage of the staged heat treatment is at a temperature of 120° C. for 5 hours, and the second stage is at a temperature of 200° C. for 2 hours.

[0042] S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor. Specifically, the crushing method is ball milling, and the material is crushed to a D50 of 3-10 μm.

[0043] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is or argon, the sintering temperature is 400° C., and the sintering time is 5 hours.

[0044] S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery. Specifically, the protective atmosphere is nitrogen, the sintering temperature is 900° C., and the sintering time is 6 hours.

[0045] Example 3 This embodiment relates to a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: Mix carbohydrate precursor, stabilizer, crosslinker, defoamer, deionized water and ethanol to obtain a mixed solution. Specifically, the carbohydrate precursor is glucose, sucrose, fructose, galactose, starch, cellulose, and curdlan; the stabilizer is phenolic resin, epoxy resin, and polyimide, and the amount of stabilizer added is 8wt.% of the amount of carbohydrate precursor added; the crosslinker is phosphoric acid, metaphosphoric acid, and pyrophosphoric acid, and the amount of crosslinker added is 12wt.% of the amount of carbohydrate precursor added; the defoamer is polyvinyl pyrrolidone, polyethylene glycol, and fatty alcohol polyoxyethylene ether, and the amount of defoamer added is 1 wt.% of the amount of carbohydrate precursor added; the amount of ethanol added is 8 wt.% of the amount of carbohydrate precursor added.

[0046] S2, spray drying: spray drying is used to dry the mixed solution obtained in step S1 to obtain a mixed precursor. Specifically, the outlet air temperature of the spray drying is 120°C and the inlet air temperature is 260°C.

[0047] S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor. Specifically, the first stage of the staged heat treatment is at a temperature of 130° C. for 4 hours, and the second stage is at a temperature of 180° C. for 4 hours.

[0048] S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor. Specifically, the crushing method is mechanical grinding and air flow powder, and the material is crushed to a D50 of 3-10 μm.

[0049] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the sintering temperature is 500° C., and the sintering time is 4 hours.

[0050] S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery. Specifically, the protective atmosphere is nitrogen and argon, the sintering temperature is 1200° C., and the sintering time is 3 hours.

[0051] Example 4 This embodiment relates to a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: Mix carbohydrate precursors, stabilizers, crosslinkers, defoamers, deionized water and ethanol to obtain a mixed solution. Specifically, the carbohydrate precursors are glucose, sucrose, fructose, galactose, starch, cellulose, curdlan, dextran, arabinan, and xylose; the stabilizers are phenolic resin, epoxy resin, polyimide, polyfurfuryl alcohol, and lignin, and the amount of stabilizer added is 3wt.% of the amount of carbohydrate precursor added; the crosslinkers are phosphoric acid, metaphosphoric acid, pyrophosphoric acid, and sulfuric acid, and the amount of crosslinker added is 14wt.% of the amount of carbohydrate precursor added; the defoamers are polyvinyl pyrrolidone, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, fatty alcohol polyethylene glycol ester, fatty acid glyceride, and polyol, and the amount of defoamer added is 2 wt.% of the amount of carbohydrate precursor added; the amount of ethanol added is 15 wt.% of the amount of carbohydrate precursor added.

[0052] S2, spray drying: spray drying is used to dry the mixed solution obtained in step S1 to obtain a mixed precursor. Specifically, the outlet air temperature of the spray drying is 140°C and the inlet air temperature is 230°C.

[0053] S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor. Specifically, the first stage of the staged heat treatment is at a temperature of 150° C. for 3 hours, and the second stage is at a temperature of 180° C. for 7 hours.

[0054] S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor. Specifically, the crushing method is mechanical grinding and air flow powder, and the material is crushed to a D50 of 3-10 μm.

[0055] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the sintering temperature is 700° C., and the sintering time is 2 hours.

[0056] S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery. Specifically, the protective atmosphere is nitrogen and argon, the sintering temperature is 1500° C., and the sintering time is 4 hours.

[0057] Example 5 This embodiment relates to a method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, comprising the following steps: S1. Premixing of raw materials: Mix carbohydrate precursor, stabilizer, crosslinker, defoamer, deionized water and ethanol to obtain a mixed solution. Specifically, the carbohydrate precursor is glucose, sucrose, fructose, galactose; the stabilizer is phenolic resin, epoxy resin, and the amount of stabilizer added is 10wt.% of the amount of carbohydrate precursor added; the crosslinker is phosphoric acid, metaphosphoric acid, and the amount of crosslinker added is 12wt.% of the amount of carbohydrate precursor added; the defoamer is polyvinyl pyrrolidone, polyethylene glycol, and the amount of defoamer added is 0.5wt.% of the amount of carbohydrate precursor added; the amount of ethanol added is 20 wt.% of the amount of carbohydrate precursor added.

[0058] S2, spray drying: spray drying is used to dry the mixed solution obtained in step S1 to obtain a mixed precursor. Specifically, the outlet air temperature of the spray drying is 150°C and the inlet air temperature is 260°C.

[0059] S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor. Specifically, the first stage of the staged heat treatment has a treatment temperature of 160° C. and a treatment time of 3 h; the second stage has a treatment temperature of 150° C. and a treatment time of 8 h.

[0060] S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor. Specifically, the crushing method is mechanical grinding and air flow powder, and the material is crushed to a D50 of 3-10 μm.

[0061] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering under a protective atmosphere to obtain a pre-carbonized material. Specifically, the protective atmosphere is nitrogen and argon, the sintering temperature is 800° C., and the sintering time is 3 hours.

[0062] S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery. Specifically, the protective atmosphere is nitrogen and argon, the sintering temperature is 1600° C., and the sintering time is 4 hours.

[0063] Application Example 1 This embodiment relates to a carbohydrate-based sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Premixing of raw materials: Mix starch precursor, lignin, phosphoric acid, polyvinyl pyrrolidone, deionized water and ethanol to obtain a mixed solution. The added amounts of lignin, phosphoric acid, polyvinyl pyrrolidone and ethanol are 2.3, 6.0, 1.0 and 15 wt.% of the added amount of starch, respectively.

[0064] S2. Spray drying: The mixed solution obtained in step S1 is dried by spray drying to obtain a mixed precursor, wherein the outlet air temperature of the spray drying is 120° C. and the inlet air temperature is 280° C.

[0065] S3, cross-linking reaction: The mixed precursor obtained in step S2 is subjected to two-stage heat treatment in air atmosphere to obtain a cross-linked precursor, wherein the treatment temperature in stage 1 is 130° C. and the treatment time is 3 h; the treatment temperature in stage 2 is 220° C. and the treatment time is 2.5 h.

[0066] S4, crushing and refining: the cross-linked precursor obtained in step S3 is crushed by mechanical grinding and air flow powder in turn to obtain a cross-linked precursor with a D50 of 8 μm.

[0067] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering in a nitrogen atmosphere, the sintering temperature is 600° C., the sintering time is 2 h, and a pre-carbonized material is obtained.

[0068] S6. High-temperature sintering: The pre-carbonized material obtained in step S5 is subjected to high-temperature sintering in a nitrogen atmosphere at a sintering temperature of 1300° C. for 5 hours to obtain the hard carbon negative electrode material of Application Example 1.

[0069] Comparative Example 1 This embodiment relates to a carbohydrate-based sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Premixing of raw materials: Mix starch precursor, deionized phosphoric acid water and ethanol to obtain a mixed solution, wherein the amount of phosphoric acid and ethanol added is 6.0 and 15 wt.% of the amount of starch added, respectively.

[0070] S2. Spray drying: The mixed solution obtained in step S1 is dried by spray drying to obtain a mixed precursor, wherein the outlet air temperature of the spray drying is 120° C. and the inlet air temperature is 280° C.

[0071] S3, cross-linking reaction: The mixed precursor obtained in step S2 is subjected to two-stage heat treatment in air atmosphere to obtain a cross-linked precursor, wherein the treatment temperature in stage 1 is 130° C. and the treatment time is 3 h; the treatment temperature in stage 2 is 220° C. and the treatment time is 2.5 h.

[0072] S4, crushing and refining: the cross-linked precursor obtained in step S3 is crushed by mechanical grinding and air flow powder in turn to obtain a cross-linked precursor with a D50 of 8 μm.

[0073] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering in a nitrogen atmosphere, the sintering temperature is 600° C., the sintering time is 2 h, and a pre-carbonized material is obtained.

[0074] S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering in a nitrogen atmosphere at a sintering temperature of 1300° C. for a sintering time of 5 h to obtain the hard carbon negative electrode material of comparative example 1.

[0075] Comparative Example 2 This embodiment relates to a carbohydrate-based sodium ion battery hard carbon negative electrode material, and the preparation method thereof comprises the following steps: S1. Premixing of raw materials: Mix starch precursor, lignin, polyvinyl pyrrolidone, deionized water and ethanol to obtain a mixed solution, wherein the added amounts of lignin, polyvinyl pyrrolidone and ethanol are 2.3, 1.0 and 15 wt.% of the added amount of starch, respectively.

[0076] S2. Spray drying: The mixed solution obtained in step S1 is dried by spray drying to obtain a mixed precursor, wherein the outlet air temperature of the spray drying is 120° C. and the inlet air temperature is 280° C.

[0077] S3, cross-linking reaction: The mixed precursor obtained in step S2 is subjected to two-stage heat treatment in air atmosphere to obtain a cross-linked precursor, wherein the treatment temperature in stage 1 is 130° C. and the treatment time is 3 h; the treatment temperature in stage 2 is 220° C. and the treatment time is 2.5 h.

[0078] S4, crushing: using mechanical grinding and air flow powder in turn to crush the cross-linked precursor obtained in step S3 to obtain a cross-linked precursor with a D50 of 8 μm.

[0079] S5, low temperature sintering: the cross-linked precursor obtained in step S4 is subjected to low temperature sintering in a nitrogen atmosphere, the sintering temperature is 600° C., the sintering time is 2 h, and a pre-carbonized material is obtained.

[0080] S6. High-temperature sintering: The pre-carbonized material obtained in step S5 is subjected to high-temperature sintering in a nitrogen atmosphere at a sintering temperature of 1300° C. for 5 h to obtain the hard carbon negative electrode material of comparative example 2.

[0081] In the step S3 of Application Example 1 and Comparative Example 2, the mixed precursor maintained a good powdery morphology during the heat treatment process, and did not melt or foam. In the step S3 of Comparative Example 2, the mixed precursor melted, foamed, and expanded severely during the pyrolysis process. The comparison results show that the proppant and defoamer can significantly improve the melting and foaming phenomena and enhance the processability of the material.

[0082] In order to effectively evaluate the technical effect of the present invention, the application example 1 and the comparative examples 1-2 were tested as follows: The constant current charge and discharge test measured that the first week charge capacity of Example 1, Comparative Example 1 and Comparative Example 2 were 364, 312 and 282 mAh / g, respectively. The first week charge capacity of Example 1 was significantly improved, which was attributed to the fact that during the cross-linking reaction, the hydrogen bond network in the carbohydrate was destroyed under the action of oxygen, and a large number of active hydroxyl groups were released, and the active hydroxyl groups then reacted with the hydroxyl groups in the cross-linking agent to form a cross-linked structure. In addition, the chemical bonds with poor thermal stability continued to break to produce a large amount of escaping gas, and a developed interconnected pore structure was formed inside the cross-linked structure during the gas escape process. In the subsequent high-temperature sintering process, an ordered carbon layer is gradually formed, and the curved carbon layer wraps the pore structure to form a developed internal pore structure, thereby improving the sodium storage capacity of the hard carbon material.

[0083] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material, characterized in that The following steps are involved: S1. Premixing of raw materials: mixing a carbohydrate precursor, a stabilizer, a crosslinking agent, a defoaming agent, deionized water and ethanol to obtain a mixed solution; S2, spray drying: using spray drying to dry the mixed solution obtained in step S1 to obtain a mixed precursor; S3, cross-linking reaction: heat-treating the mixed precursor obtained in step S2 in stages to obtain a cross-linked precursor; S4, crushing and refining: crushing the cross-linked precursor obtained in step S3 to obtain a refined cross-linked precursor; S5, low temperature sintering: sintering the cross-linked precursor obtained in step S4 at low temperature under a protective atmosphere to obtain a pre-carbonized material; S6: high temperature sintering: the pre-carbonized material obtained in step S5 is subjected to high temperature sintering under a protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery.

2. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the first stage of the staged heat treatment has a treatment temperature of 120-160°C and a treatment time of 2-5 hours; the second stage of the heat treatment has a treatment temperature of 150-250°C and a treatment time of 2-8 hours.

3. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the stabilizer is one or more of phenolic resin, epoxy resin, polyimide, polyfurfuryl alcohol, and lignin; the amount of the stabilizer added is 1-10wt.% of the amount of the carbohydrate precursor added.

4. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the cross-linking agent is one or more of phosphoric acid, metaphosphoric acid, pyrophosphoric acid and sulfuric acid; the added amount of the cross-linking agent is 5-20wt.% of the added amount of the carbohydrate precursor.

5. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the defoaming agent is one or more of polyvinyl pyrrolidone, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, fatty alcohol polyethylene glycol ester, fatty acid glyceride, and polyol; the added amount of the defoaming agent is 0.5-3 wt.% of the added amount of the carbohydrate precursor.

6. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the amount of ethanol added is 5-20 wt.% of the amount of carbohydrate precursor added.

7. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S6, the protective atmosphere is nitrogen and / or argon, the sintering temperature is 900-1600°C, and the sintering time is 2-6 hours.

8. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the outlet air temperature of the spray drying is 110-150°C, and the inlet air temperature is 200-320°C.

9. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the carbohydrate precursor is one or more of glucose, sucrose, fructose, galactose, starch, cellulose, curdlan, dextran, arabinan, and xylose.

10. The method for preparing a carbohydrate-based sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S4, the crushing method is one or more of mechanical grinding, air flow grinding, Raymond milling, ball milling, and stirring milling, and the material is crushed to a D50 of 3-10 μm; In step S5, the protective atmosphere is nitrogen and / or argon, the sintering temperature is 400-800°C, and the sintering time is 1-5h.

Citation Information

Patent Citations

  • Preparation method of composite carbon source sodium ion battery hard carbon negative electrode material

    CN118206105A

  • Hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN118754100A

  • Method for preparing hard carbon negative electrode material from cellulosic biomass and product thereof, and use of product

    WO2024207302A1